Investigating Students’ Problem Selft-Taught in English Learning - Ilhamuddin Ilhamuddin; Andi Sadapotto; Ibrahim Manda; Sam Hermansyah; Muhammad Hanafi; Syamsu T (Universitas Muhammadiyah Enrekang, 2024)
The aim of of this research to determine the independen learning problems of odd semester students at Muhammadiyah Sidenreng Rappang University. This research uses descriptive qualitative methods as research methodology. This research was conducted to determine students' autodidactic learning problems. The population in this research were 24 Muhammadiyah Sidenreng Rappang University students from semester 1. The data collection methods used in this research were questionnaires and interviews. The research results show that students' autodidactic learning problems have a big impact on the way they learn when they learn on their own. Autodidactic student learning problems can be caused by several things, namely, not being able to learn on their own, lack of understanding, fear of making mistakes, lack of guidance and lack of learning motivation to learn autodidactically.